2020
DOI: 10.3390/ijerph17176395
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices of Healthcare Professionals on COVID-19 and Risk Assessment to Prevent the Epidemic Spread: A Multicenter Cross-Sectional Study from Punjab, Pakistan

Abstract: In the current outbreak of novel coronavirus (COVID-19), healthcare professionals (HCPs) have a primary role in combating the epidemic threat. HCPs are at high risk of not only contracting the infection but also spreading it unknowingly. It is of utmost importance to evaluate their knowledge, attitudes, and practices (KAP) and the ability to assess the risks associated with the outbreak. A cross-sectional online survey involving physicians, pharmacists, and nurses was conducted. A 39-itemed questionnaire based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 23 publications
9
41
0
1
Order By: Relevance
“…The mean age and most prevalent age group recorded in this study is similar to that reported in a study done in south-south, Nigeria, where the mean age of respondents was 33.6 ± 9.3 years, with majority of respondents in the age group, 31-40 years [ 8 ]. Majority of the health workers in this study were females and this was also seen in similar studies [ 8 , 9 ]. The level of education recorded in this study was secondary and tertiary level of education.…”
Section: Discussionsupporting
confidence: 87%
“…The mean age and most prevalent age group recorded in this study is similar to that reported in a study done in south-south, Nigeria, where the mean age of respondents was 33.6 ± 9.3 years, with majority of respondents in the age group, 31-40 years [ 8 ]. Majority of the health workers in this study were females and this was also seen in similar studies [ 8 , 9 ]. The level of education recorded in this study was secondary and tertiary level of education.…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, there are concerns that COVID-19 could further overwhelm the healthcare system. Having said this, knowledge, attitude and practices toward COVID-19 appeared satisfactory among healthcare professionals in Pakistan with a high percentage having a positive attitude toward prevention and management; however, there were some misconceptions that need to be addressed going forward (90,91). There were concerns though about the extent of preventative practices among university students and employees despite good knowledge and attitudes toward COVID-19 (92).…”
Section: General and Asiamentioning
confidence: 97%
“…The current literature indicates a conflicting picture regarding HCWs' KAP regarding COVID19. Some studies [11][12][13][14] have indicated that HCWs have good knowledge of and positive attitude toward COVID-19 as well as practice safer infection, prevention and control practices put forward by international and local health authorities. On the other hand, an Ethiopian study reported poor prevention practices toward COVID-19 among HCWs 15 while close to half of HCWs in Nepal were reported to have negative attitudes toward COVID-19.…”
Section: Introductionmentioning
confidence: 99%